Building systems for interior designers - Binggeli, Corky (Hoboken, New Jersey : John Wiley & Sons, Inc., 2016)
"The ultimate interior designer's guide to building systems and safety Building Systems for Interior Designers, Third Edition is the single-source technical reference that every designer needs, and an ideal solution for NCIDQ exam preparation. Now in its third edition, this invaluable guide has been updated to better address the special concerns of the interior designer within the context of the entire design team." -- Book
Preface xi -- Acknowledgments xii -- Part I The building, the environment, and health and safety -- Chapter 1 Environmental conditions and the site 3 -- Chapter 2 Designing for the environment 19 -- Chapter 3 Designing for human health and safety 41 -- Part II Building components -- Chapter 4 Building forms, structures, and elements 53 -- Chapter 5 Floor/ceiling assemblies, walls, and stairs 70 -- Chapter 6 Windows and doors 83 -- Part III Acoustics -- Chapter 7 Acoustic design principles 105 -- Chapter 8 Architectural acoustics 114 -- Part IV Water and waste systems 145 -- Chapter 10 Waste and reuse systems 164 -- Chapter 11 Fixtures and appliances 176 -- Part V Heating, cooling, and ventilation systems -- Chapter 12 Principles of thermal comfort 205 -- Chapter 13 Indoor air quality,ventilation, and moisture control 222 -- Chapter 14 Heating and cooling 243 -- Part IV Electrical and lighting systems -- Chapter 15 Electrical system basics 275 -- Chapter 16 Electrical distribution 288 -- Chapter 17 Lighting systems 313 -- Part VII Fire safety, conveyance, security, and communications -- Chapter 18 Fire safety design 347 -- Chapter 19 Conveyance systems 376 -- Chapter 20 Communications, security, and control equipment 390 -- Bibliography 398 -- Index 399
Includes bibliographical references and index.
English
Keywords: Buildings -- Environmental engineering; Buildings -- Design and construction -- Mechanical equipment; Buildings -- Design and construction -- Electric equipment